Functional integration design and aerodynamic characterization of a hexacopter agricultural unmanned aerial vehicle based on its appearance - Liu, Zhe (Frontiers in Mechanical Engineering, 2024)
As an advanced agricultural technology equipment, the functional integration design and appearance aerodynamic characteristics of hexacopter agricultural UAV are significant for improving the efficiency of agricultural production. Firstly, the study carried out the functional integration design of the hexacopter agricultural UAV, and completed the matching analysis and selection of the relevant components of the power system. Then, the numerical simulation method of computational fluid dynamics was used to analyze the aerodynamic characteristics of the UAV. Finally, the role of different propeller pitch on important parameters such as lift and range time of the UAV was verified. The results showed that in the XY section of the UAV, namely, the surface parallel to the flight direction, the areas with high streamline velocity were mainly concentrated at the intersection of the airflow with the landing gear and the motor. The streamlines in the front of the UAV were tightly and neatly distributed, while those in the rear were sparser. The motor force efficiencies of the UAVs with different propeller pitches ranged from 7.05 to 7.25 g/w. At a flight speed of 5 m/s, the motor force effect of the UAV with a pitch of 260 mm reached 7.25 g/w, which was the highest value among all models. Meanwhile, it had the longest endurance time of 19.14 min, indicating the best performance. The results suggested that it not only promoted the modernization of agricultural UAVs but also effectively enhanced the efficiency of agricultural production.